Voice Outcome after Gore-Tex Medialization Thyroplasty - Elnashar, Ismail; El-Anwar, Mohammad; Amer, Hazem; Quriba, Amal (International Archives of Otorhinolaryngology, 2015)
Introduction Although medialization thyroplasty utilizing Gore-Tex (Gore and Associates, Newark, Delaware, United States) has been discussed in the literature, few reports have assessed voice quality afterward, and they did not use a full assessment protocol.Objective To assess the improvement in voice quality after medialization thyroplasty utilizing Gore-Tex in patients with glottic insufficiency of variable etiology.Methods Eleven patients with glottic insufficiency of different etiologies that failed compensation were operated by type 1 thyroplasty utilizing Gore-Tex. Pre- and postoperative (1 week, 3 months, and 6 months) voice assessment was done and statistical analysis was performed on the results.Results In all postoperative assessments, there was significant improvement in the grade of dysphonia (p < 0.004) and highly significant reduction in the size of glottic gap and prolongation of maximum phonation time (p < 0.0001). The difference in voice parameters in the early (1 week) and the late (3 and 6 months) postoperative period was not significant. None of the patients developed stridor or shortness of breath necessitating tracheotomy, and there was no implant extrusion in any patient during the study period.Conclusion Gore-Tex medialization provides reliable results for both subjective and objective voice parameters. It leads to a satisfactory restoration of voice whatever the etiology of glottic incompetence is. This technique is relatively easy and does not lead to major complications. Further studies with larger number of patients and more extended periods of follow-up are still required to assess the long-term results of the technique regarding voice quality and implant extrusion.
Keywords: thyroplasty; voice; Gore-Tex